Correlations between physical activity and well-being status in young adults - Mahardika, Nanda Dwi; Rahman, Farid (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction.The civilisation revolution caused by Society 5.0 has predisposed public health to reduced physical activity globally, from the developmental period of childhood to old age. The transition process of technological development, social change, and economic growth has altered population demographics, which signiﬁcantly impacts public health and is the pri-mary factor in the decline in physical activity levels in superpower countries such as the United States of America and developing countries such as China.Methods. This non-experimental study used a descriptive quantitative research design with a cross-sectional approach.Results. Signiﬁcant two-tailed correlations were found between physical activity and physical activity (r = 0.260, p < 0.001), health (r = 0.159, p < 0.001), occupational (r = 0.177, p < 0.001), emotional (r = 0.100, p = 0.046), and nutritional (r = 0.110, p < 0.027) well-being dimensions. However, there was no correlation between physical activity and religion (r = 0.260, p < 0.080) and friends and family (r = 0.069, p < 0.172) well-being dimensions.Conclusions. Physical activity correlated signiﬁcantly with the physical activity, health, occupational, emotional, and nutritional well-being dimensions, while the religious and friends and family dimensions showed no signiﬁcant correlation.
Keywords: young adults; well-being; physical activity